2014
DOI: 10.3988/jcn.2014.10.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Axon Count and Sympathetic Skin Responses in Lumbosacral Radiculopathy

Abstract: Background and PurposeElectrodiagnostic studies can be used to confirm the diagnosis of lumbosacral radiculopathies, but more sensitive diagnostic methods are often needed to measure the ensuing motor neuronal loss and sympathetic failure.MethodsTwenty-six patients with lumbar radiculopathy and 30 controls were investigated using nerve conduction studies, motor unit number estimation (MUNE), testing of the sympathetic skin response (SSR), quantitative electromyography (QEMG), and magnetic resonance myelography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
1
11
3
Order By: Relevance
“…The MUNE values of the present study and those of Tilki et al . are about two‐ to threefold larger than a previous report of 43 motor units .…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…The MUNE values of the present study and those of Tilki et al . are about two‐ to threefold larger than a previous report of 43 motor units .…”
Section: Discussioncontrasting
confidence: 88%
“…We found that the number of the AH motor units was slightly greater than the mean of 98 units reported by Tilki and coworkers, who used incremental MUNE. Our estimate is consistent with the modestly lower estimate of approximately 100 motor units in individual hand muscles, which likely have a slightly smaller cross‐sectional area than the AH .…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Thus, sympathetic activity is assessed as rapid and painless. SSR has been evaluated in a variety of diseases such as migraine, multiple sclerosis, fibromyalgia, and lumbosacral radiculopathy [5][6][7][8]. In addition, SSR has been evaluated in skin diseases such as leprosy, palmoplantar hyperhidrosis, vitiligo and psoriasis [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%